The Role of the P2X7 Receptor in Cancer Development and Progression - Yusupovna, Mamatova Irodakhon; Numonovna, Muydinova Dilnoza; Abdujalilovich, Mamajonov Zafar; Aʼzamjon oʻgʻli, Maxammadjonov Tursunboy; Erkinjonovna, Fozilova Gavxaroy; Muzaffarjon o’g’li, Boqiyev Mirzoxid (Journal of Neonatal Surgery, 2025)
N\A